Announcements of plot in Genesis - Turner, Laurence A. (Journal for the study of the Old Testament. Supplement series, 1990)
The four narrative blocks which comprise Genesis are prefaced by statements ('Announcements') which suggest ways in which the ensuing stories are likely to develop. The author concludes that the 'Announcements' influence their narratives in many different ways and that they are misleading indicators of how plots will develop. Genesis is more concerned to present the ironies of human motive and divine providence than to recount the working out of any pre-ordained plan on God's part. This original and refreshing monograph, written in a vigorous style, is certain to alter the way readers remember.